RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) TERHADAP DOSIS BOKASHI BATANG PISANG DAN NPK MUTIARA 16:16:16 DI MAIN-NURSERY - Bagus Pramuji; Fathurrahman (DINAMIKA PERTANIAN, 2023)
The aim was to determine the growth response of oil palm seedlings (Elaeis guineensis Jacq) in the main-nursery to the interaction of banana stem bokashi doses and pearl NPK fertilizer (16:16:16). This research was carried out on the experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru City, for 5 months, starting in September 2021 and ending in January 2022. The design used in this study was a factorial, completely randomized design (CRD) consisting of two factors. The first factor was banana stem bokashi fertilizer (B), consisting of four, namely without bokashi, 800, 1,600, and 2,400 g/plant. The second factor was pearl NPK 16:16:16, consisting of 4 levels, namely without NPK, 11.25, 22.50, and 33.75 g/plant, 16 treatment combinations were obtained with 3 replications, so there were 48 experimental units. Parameters observed were an increase in plant height, an increase in the number of fronds, an increase in the length of the longest frond, an increase in stem circumference, root length, and root volume. The data were analyzed statistically and continued with an HSD level of 5%. The results showed that the interaction of banana stem bokashi fertilizer and pearl NPK 16:16:16 gave a real response to all parameters. The best responses were to bokashi fertilizer (2,400 g/plant) and pearl NPK (16:16:16) at 33.75 g/plant.